Investigation of microorganisms involved in kefir biofilm formation - Han, Xue; Zhang, Li-Juan; Wu, Hui-Ying; Wu, Yi-Fan; Zhao, Sai-Nan (Antonie van Leeuwenhoek, 2018)
Kefir is a natural fermentation agent composed of various microorganisms. To address the mechanism of kefir grain formation, we investigated the microbial role in forming kefir biofilms. The results showed that a biofilm could be formed in kefir-fermented milk and the biofilm forming ability reached the maximum at 13 days. The strains Kluyveromyces marxianus , Lactococcus lactis , Leuconostoc mesenteroides , Lactobacillus kefiri , Lactobacillus sunkii and Acetobacter orientalis were isolated from kefir biofilms by the streak-plate method. These microorganisms were analysed with respect to biofilm forming properties, including their surface characterisation (hydrophobicity and zeta potentials) and the microbial aggregation. The results indicated that Klu. marxianus possessed the strongest biofilm forming properties with the strongest hydrophobicity, lowest zeta potential and greatest auto-aggregation ability. When Klu. marxianus and Ac. orientalis were co-cultured with kefir LAB strains respectively, it was found that mixing Klu. marxianus with Lb. sunkii produced the highest co-aggregation ability. These results elucidated the mechanism of kefir biofilm formation and the microorganisms involved.